Predselitvena disperzija kmečke lastovke Hirundo rustica v Sloveniji - Potokar, Maja (Acrocephalus, 2000)
The present contribution presents the analysis made on recoveries of first year and adult Barn Swallows Hirundo rustica in Slovenia during 1992-1998. Birds were ringed and recaptured within the same summer. The purpose of this analysis was to establish the following: (a) do these movements occur only amongst first year birds or amongst adult birds as well, (6) which are the direo- tions of movements> (c) is there any preferred direction, (d) what are the distances of movements and (e) if and how the pre-migratory movements change during the summer. The greatest number of recoveries, which indicate certain pre-migratory dispersion, was among first year birds. Some recoveries,which also show pre-migratory dispersion, were made as early as in July; in August the number of these recoveries increased a great deal, while in September the number fell. Dispersion of first year birds was the greatest in August. Statistic analysis (chi square - test) has shown that during the first year Barn Swallows have random movements. Among adult birds there were only a few long distance recoveries during the breeding season. Adults begin to migrate earlier than first year birds. In spite of the fact that their migration starts at the end of August, some recoveries have shown that they can stay in the area of Slovenia until mid-September. Some of these adults probably stayed in the area of Slovenia for a longer period, but it is not known whether they bred there.
Keywords: bird; Birds; ptice; Behavior, animal; ornitologija; Ecosystem; lastovke; selitev; Age factors; Slovenia; Slovenija